DASAR-DASAR ILMU: ONTOLOGI DAN EPISTEMOLOGI - Harif Rahman Suyatno; Efendi Efendi; Muhammad Zalnur (CV. Adiba Aisha Amira, 2025)
This study aims to explain the essence of ontology, its relation to science, and its connection with epistemology. The problem discussed concerns how ontology provides a foundation for understanding reality and how epistemology explains the origin, method, and validity of knowledge. The method used is literature review by examining philosophical perspectives. The results indicate that ontology addresses universal existence as the basis of general metaphysics, science systematically explains reality through research, and epistemology explores how knowledge is obtained and validated. Together, they complement each other as the foundation of the philosophy of science.